Conversion of polymer wastes & energetics - Krause, H. H. 1950-; Penninger, Johannes M. L., 1942- (ChemTec Pub., 1994)
This book shares recycling developments in Germany and Italy. Several chapters deal with various methods of waste processing, including pyrolysis, hydrogenation, composting, and conversion to a powder coating.
Keywords: Plastic scrap -- Recycling.; Polymers -- Recycling.; Explosive ordnance disposal.; Propellants -- Environmental aspects.; Hazardous wastes.; elektronické knihy; electronic books